Association between Personality Traits and Metacognition among Pharmacy Students: Implication for Pharmaceutical Education - Hu, Xianmin; Wang, Jun; Liu, Juan; Yao, Yuhang (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: The importance of pharmacy practitioners’ personality traits in their professional development and future patient-centered pharmaceutical care practice has been widely recognized. Metacognitive skills in critical thinking, self-directed learning as a critical part of pharmacy training has been emphasized in the new pharmacy education accreditation standard. Correlation between metacognition and personality has been demonstrated in patients with personality pathology. Objectives: This work aimed to study the association between personality and metacognition among Chinese pharmacy students. Materials and Methods: A total of 130 pharmacy students voluntarily completed the 30-item Metacognitions Questionnaire (MCQ-30) and NEO Five-Factor Inventory (NEO-FFI) to measure their metacognitions and personality traits, respectively. Results: Pearson Correlations showed a strong association between metacognition and NEO-FFI conscientiousness personality trait. NEO-FFI neuroticism was found weakly but significantly positively associated with overall MCQ-30 scores, strongly positively associated with metacognitive factors “Negative beliefs about worry” and “Cognitive self-consciousness”, moderately negatively associated with “Positive beliefs about worry” or “Cognitive confidence” subscales of MCQ-30. Scores on the NEO-FFI extraversion, openness or agreeableness and the metacognitive factor “Positive beliefs about worry”, “Cognitive confidence” or “Negative beliefs about worry” were highly correlated. Conclusion: This study firstly linked pharmacy students’ personality traits to their metacognition levels, suggesting that educational interventions to develop metacognitive skills might contribute to the improvement of students’ personality traits.
Keywords: Personality; Metacognition; Association; Pharmacy students; Pharmaceutical; education